PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA DALAM KONSEP SISTEM INDERA PADA SISWA KELAS XI SMA - Rasyid, Magfirah; Azis, Andi Asmawati; Saleh, Andi Rahmat (Jurnal Pendidikan Biologi, 2016)
Instructional media can showed what the teacher can’t say with words, so that the abstract can be more real with the instructional media. This research is a research and development, aims to produce media-based learning multimedia wich is valid, effective and practical. This research use software Ashampoo MyAutoplay, concept of sense systems in Class XI MAN 2 Model Makassar. This research was conducted using the integrated development model Plomp with Luther's development model. The subjects were students of class XI IPA4 MAN 2 Model Makassar. Techniques of data collection in this study there are three, namely validity, obtained through a validation by the validator; effectiveness, acquired through learning achievement and students' response to instructional media; practicality, obtained by evaluation  of  instrument by validator. The results showed that the average value of the total validity of the validator is 3.6. Media effectiveness obtained student’s learning achievement showed 91.9% and student responses showed 91.6% o. Practicality media obtained from assessment validator with the results validity 3.7.